R-powered Excel for analytics (O'Reilly Media, Inc., 2022)
If you’re using Excel to collect, analyze, and interpret business data, you may be running into limitations that stop you from performing advanced, reproducible analysis. Speed up, automate, and validate your reporting and analytics with R, the popular open source programming language for data science. Join expert George Mount to learn how to utilize R for data manipulation by focusing on the most common data structures in business analytics: vectors and data frames. You’ll gain hands-on experience in the RStudio Desktop and learn how to use R’s popular tidyverse collection of packages for data analytics. Along the way, you’ll walk through the various windows in RStudio, discover how to navigate an R development environment, and understand how R can augment and automate common data preparation and manipulation tasks often done in Excel.